Twelve steps to a compassionate life - Armstrong, Karen, 1944- (KARACHI OXFORD, 2011)
Taking as her starting point the teachings of the great world religions, Karen Armstrong demonstrates in twelve practical steps how we can bring compassion to the forefront of our lives. Armstrong argues that compassion is inseparable from humanity, and by transcending the limitations of selfishness on a daily basis we will not only make a difference in the world but also lead happier, more fulfilled, lives.
The first step : learn about compassion -- The second step : look at your world -- The third step : compassion for yourself -- The fourth step : empathy -- The fifth step : mindfulness -- The sixth step : action -- The seventh step : how little we know -- The eighth step : how should we speak to one another? -- The ninth step : concern for everybody -- The tenth step : knowledge -- The eleventh step : recognition -- The twelfth step : love your enemies -- A last word.
"A Borzoi book."--T.p. verso.
Includes bibliographical references (p. 199-222).
Keywords: Compassion; Twelve-step programs